Birth Place Preference and Birth Attendant Selection during Covid-19 Pandemic in Tarakan City, North Kalimantan - Ariyanti, Ririn; Yulianti, Ika; Padlilah, Rahmi (Journal of Maternal and Child Health, 2021)
Background: Childbirth assistance during the Covid 19 pandemic needs attention to reduce maternal mortality rate and infant mortality rate. This study aimed to analyze the factors influencing the choice of place and birth attendant during the Covid 19 pandemic in Tarakan City.Subjects and Method: This was an obser